Measurement of D mesons production in deep inelastic scattering at HERA - Gwenlan, C; Cooper-Sarkar, A; Devenish, R; Foster, B; Walczak, R; Zeus Collaboration (317 others) (Institute of Physics, 2007)
Charm production in deep inelastic scattering has been measured with the ZEUS detector at HERA using an integrated luminosity of 82 pb^−1. Charm has been tagged by reconstructing D∗+, D0, D+ and D+s (+ c.c.) charm mesons. The charm hadrons were measured in the kinematic range pT(D∗+, D0, D+) > 3 GeV, pT(D+s) > 2 GeV and |η(D)| < 1.6 for 1.5 < Q2 < 1000 GeV^2 and 0.02 < y < 0.7. The production cross sections were used to extract charm fragmentation ratios and the fraction of c quarks hadronising into a particular charm meson in the kinematic range considered. The cross sections were compared to the predictions of next-to-leading-order QCD, and extrapolated to the full kinematic region in pT (D) and η(D) in order to determine the open-charm contribution, Fc¯ c2 (x, Q^2), to the proton structure function F2.